2019
DOI: 10.1038/s41597-019-0293-1
|View full text |Cite
|
Sign up to set email alerts
|

Full-length transcriptome sequencing from multiple tissues of duck, Anas platyrhynchos

Abstract: Duck (Anas platyrhynchos), one of the most economically important waterfowl, is an ideal model for studying the immune protection mechanism of birds. An incomplete duck reference genome and very limited availability of full-length cDNAs has hindered the identification of alternatively spliced transcripts and slowed down many basic studies in ducks. We applied PacBio Iso-Seq technologies to multiple tissues from duck for use in transcriptome sequencing. We obtained 199,993 full-length transcripts and comprehens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 38 publications
4
26
1
Order By: Relevance
“…Due to the lack of detailed full-length cDNA data and high-quality genome annotation, there are few studies about AS in ducks or other birds [ 31 , 32 ]. Yin et al (2019) found that a total of 199,993 full-length transcripts were obtained from 8 duck tissues by using transcriptome sequencing, and 35,031 AS events were accurately predicted from 3346 genes, which is very useful for the functional research of other birds [ 33 ]. In our study, an average of 37,267 AS events were counted from each sample, and the number of AS in each sample were mainly concentrated in TSS and TTS, which indicated that the AS of duck skeletal muscle growth and development mainly existed in the first exon and the last exon.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of detailed full-length cDNA data and high-quality genome annotation, there are few studies about AS in ducks or other birds [ 31 , 32 ]. Yin et al (2019) found that a total of 199,993 full-length transcripts were obtained from 8 duck tissues by using transcriptome sequencing, and 35,031 AS events were accurately predicted from 3346 genes, which is very useful for the functional research of other birds [ 33 ]. In our study, an average of 37,267 AS events were counted from each sample, and the number of AS in each sample were mainly concentrated in TSS and TTS, which indicated that the AS of duck skeletal muscle growth and development mainly existed in the first exon and the last exon.…”
Section: Discussionmentioning
confidence: 99%
“…The combined use of these platforms and library preparation chemistries can generate high-quality and throughput data on full-length transcripts. LRS has been applied for the assembly of transcriptomic maps in several organisms (Sharon et al, 2013 ; Tilgner et al, 2015 ; Sessegolo et al, 2019 ; Yin et al, 2019 ; Zhao et al, 2019 ; Roach et al, 2020 ), including viruses (Tombácz et al, 2016 , 2019 ; Balázs et al, 2017 ; Moldován et al, 2017 ; Prazsák et al, 2018 ; Depledge et al, 2019 ; O'Grady et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Amplified cDNA-sequencing -from different time points Samples from each time point (4,8,12, and 20 h p.i.) were sequenced by the ONT MinION device using the cDNA-PCR Barcoding protocol (SQK-PCS109 and SQK-PBK004; Version: PCSB_9086_v109_revK_14Aug2019).…”
Section: Library Preparation For Nanopore Sequencingmentioning
confidence: 99%